2016
DOI: 10.1002/j.0022-0337.2016.80.5.tb06111.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Dental Students’ Attitudes About Treating Underserved Populations: A Longitudinal Study

Abstract: The aim of this study was to assess changes in a group of dental students' feelings about, willingness to treat, and perceived responsibility in treating underserved populations as they progressed through their predoctoral education. A questionnaire was developed to assess the first-through fourth-year (D1-D4) students' attitudes about treating 13 underserved populations after graduation. Surveys were distributed from 2008 to 2014, resulting in longitudinal data from three graduating classes (D1 year: N=240; e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 30 publications
4
48
0
Order By: Relevance
“…Community‐based education and community service‐learning are examples of experiential learning that were discussed. These “hold the potential to instill awareness of others, foment curiosity, and catalyze self‐reflection, process that may subsequently foster empathy and human compassion.” Such experiences often alleviate the stress associated with the credit and requirements‐focused weight of most dental curricula, which can impact students’ educational experiences …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Community‐based education and community service‐learning are examples of experiential learning that were discussed. These “hold the potential to instill awareness of others, foment curiosity, and catalyze self‐reflection, process that may subsequently foster empathy and human compassion.” Such experiences often alleviate the stress associated with the credit and requirements‐focused weight of most dental curricula, which can impact students’ educational experiences …”
Section: Resultsmentioning
confidence: 99%
“…This definition of school environment is also expanded to include exposure of students through externships and community experiences . Another study discussed the stressful school environment perpetrated by a heavy curriculum and how this affects students’ empathy levels, which already undergo a natural decrease throughout dental school …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental services provided by students were well-received by the homeless population. However, there is evidence that dental student attitudes' towards treating homeless people worsen as they progress through their dental course (Major et al 2016) and that despite working with underserved populations as part of their university training, dentists were unlikely to treat homeless people as part of their everyday practice (McQuistan et al 2010). Dental service providers should not operate in isolation, but work collaboratively with other homeless service providers.…”
Section: (Continued Next Page)mentioning
confidence: 99%
“…A recent longitudinal study evaluated changes in dental students' attitudes to treat underserved populations. 16 Over a six-year period, 132 dental students responded to a survey distributed at the beginning of the D1, D2, and D3 academic years and the end of the D4 year. That study found that students' feelings became more negative in the D2, D3, and D4 years about treating low-income patients, frail elderly, homebound, homeless, other ethnic groups, and non-English-speaking patients, but more positive towards treating drug users and HIV/AIDS populations.…”
mentioning
confidence: 99%